Emerging Risk Factors for Impaired Lung Function in Chemical Industry Workers of Faisalabad - Shireen Jawed, Benash Altaf, Anam Rehman, Noor-i-Kiran Naeem, Shireen Jawed, Benash Altaf, Anam Rehman, Noor-i-Kiran Naeem (Journal of Rawalpindi Medical College, 2022)
Objective: To determine the impact, obesity and age on the lung functions determined by PEFR of healthy workers of chemical industries. Methodology: This was a cross sectional study performed at private medical college of Faisalabad. Three days medical camp was arranged during 2nd to 4th September 2020 after taking approval from institutional ethical committee. All relevant information including age, residence and history about chemical exposure were recorded in a structured proforma. Obesity was determined on basis of BMI grading. BMI was calculated from estimated Height and weight PEFR of each participant was determined using Wright’s Peak flow meter. Data was analyzed by SPSS21. Results: Mean± SD age, height and weight of the studied population was 38.85 ± 12.1, 170.07 ±12.0 and 78.12 ±12.7. lowest PEFR value was found in subjects with age range 61 to 70 years as compred to youger subjects . The mean PEFR value were significantly different with respect to various age catagoeies with p value= 0.000 Highest mean PEFR values were found in taller subjects having height ≥ 180 cm and lowest values were found in subjects with height 150-159 cm, the difference in means was statisticaly significant with p value= 0.05. Morbid obese subjects showing comparatively lower PEFR values in morbid obese with significant p value =0.002. . PEFR was found to be negatively associated with age ( p- value= 0.000*) and BMI( p value =0.001*). Our results also showed weak positive association of PEFR with height, however this relation was not found to be statistically significant (p value= 0.081). Conclusion: Peak expiratory flow rate is negatively associated with increasing BMI and age, reflecting that elderly and obese subjects are more prone to have affected lung function due to exposure to chemicals